A large‐scale molecular survey of Clinostomum (Digenea, Clinostomidae). (22nd December 2014) - Locke, Sean A.; Caffara, Monica; Marcogliese, David J.; Fioravanti, Maria L.
<x xml:space="preserve">Abstract</x> Members of the genus Clinostomum Leidy, 1856 are parasites that mature in birds, with occasional reports in humans. Because morphological characters for reliable discrimination of species are lacking, the number of species considered valid has varied by an order of magnitude. In this study, sequences from the DNA barcode region of cytochrome c oxidase I (CO1) and/or internal transcribed spacer (ITS) from specimens from Mexico, Bolivia, Peru, Brazil, Kenya, China and Thailand were analysed together with published sequences from Europe, Africa, Indonesia and North America. Although ITS and CO1 distances among specimens were strongly correlated, distance‐based analysis of each marker yielded different groups. Putative species indicated by CO1 distances were consistent with available morphological identifications, while those indicated by ITS conflicted with morphological identifications in three cases. There was little overlap in sequence variation within and between species, particularly for CO1. Although ITS and CO1 distances tended to increase in specimens that were further apart geographically, this did not impair distance‐based species delineation. Phylogenetic analysis suggests a deep division between clades of Clinostomum inhabiting the New World and Old World, which parallels the distribution of their principal definitive hosts, the Ardeidae.